2023
DOI: 10.1002/jcsm.13350
|View full text |Cite
|
Sign up to set email alerts
|

Improved endurance capacity of diabetic mice during SGLT2 inhibition: Role of AICARP, an AMPK activator in the soleus

Shintaro Nakamura,
Yasutaka Miyachi,
Akihito Shinjo
et al.

Abstract: BackgroundDiabetes is associated with an increased risk of deleterious changes in muscle mass and function or sarcopenia, leading to physical inactivity and worsening glycaemic control. Given the negative energy balance during sodium–glucose cotransporter‐2 (SGLT2) inhibition, whether SGLT2 inhibitors affect skeletal muscle mass and function is a matter of concern. However, how SGLT2 inhibition affects the skeletal muscle function in patients with diabetes remains insufficiently explored. We aimed to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…AMPK is also known to be an upstream factor that promotes the organization of the mitochondrial supercomplex ( Han et al, 2022 ). Interestingly, Nakamura et al recently reported that treatment with sodium–glucose cotransporter-2 (SGLT2) inhibitors, which have been shown to significantly attenuate the progression of CKD ( Herrington et al, 2023 ), improved muscle endurance via AMPK activation in a diabetic murine model ( Nakamura et al, 2023 ). This finding suggests that activation of AMPK by HIIT with ES is at least one of the upstream signals that improve muscle endurance, promoting mitochondrial biogenesis and supercomplex formation in muscle with CKD-induced cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is also known to be an upstream factor that promotes the organization of the mitochondrial supercomplex ( Han et al, 2022 ). Interestingly, Nakamura et al recently reported that treatment with sodium–glucose cotransporter-2 (SGLT2) inhibitors, which have been shown to significantly attenuate the progression of CKD ( Herrington et al, 2023 ), improved muscle endurance via AMPK activation in a diabetic murine model ( Nakamura et al, 2023 ). This finding suggests that activation of AMPK by HIIT with ES is at least one of the upstream signals that improve muscle endurance, promoting mitochondrial biogenesis and supercomplex formation in muscle with CKD-induced cachexia.…”
Section: Discussionmentioning
confidence: 99%